Satellites orbit calculation with consideration of nonspherical form of the Earth, atmospheric drag and thrust vector - Cương, Nguyễn Đức; Tú, Hoàng Anh (Journal of Computer Science and Cybernetics, 2012)
The paper presents algorithms and program for calculation of satellite’s motion & its orbits parameters around the Earth as a point mass. The problem is solved directly by numerical method based on satellite’s motion dynamic equation with consideration of atmospheric drag, nonspherical form of the Earth and thrust vector of orbit’s correction propulsion system. Some received calculation results show the qualitative and quantitative fitness with the published results of the other authors.